Thermal diffusivity of coal and its predictive model in nitrogen and air atmospheres. (5th February 2018) - Deng, Jun; Li, Qing-Wei; Xiao, Yang; Wang, Cai-Ping; Shu, Chi-Min
Highlights: Sensitivity of coal's thermal diffusivity to temperature was investigated. Effect of atmosphere on the thermosensitivity of thermal diffusivity was studied. Predictive models for the thermal diffusivity of coal were established. Inversion of thermal diffusivity by the value at certain temperature was analyzed. Abstract: Thermal diffusivity is a thermophysical parameter that plays a vital role in heat transfer in coal mass. By considering the temperature range of 303–573 K, this study applied the laser flash method to investigate the thermal diffusivity of coal in nitrogen and air atmospheres. The change rate and thermosensitivity of thermal diffusivity were analyzed. A predictive model was established to forecast the thermal diffusivity of coal from 303 to 573 K. The results indicated that the thermal diffusivity in the nitrogen atmosphere decreased with increasing temperature, whereas that in the air atmosphere decreased first and then increased. The change rate and thermosensitivity of thermal diffusivity versus temperature presented a similar tendency to that of thermal diffusivity. Furthermore, the difference in thermosensitivity between the nitrogen and air atmospheres was not obvious until a certain temperature range (400–450 K) was reached. The tendency of thermal diffusivity versus temperature could be forecast by a predictive model. Moreover, the thermal diffusivity levels in the nitrogen atmosphere and at below 483 K in the air atmosphere could be accurately predicted.